2017
DOI: 10.1007/s11095-017-2222-3
|View full text |Cite
|
Sign up to set email alerts
|

Hemodynamic Effects of Lipid-Based Oxygen Microbubbles via Rapid Intravenous Injection in Rodents

Abstract: LOMs may be injected in quantities sufficient to deliver clinically meaningful volumes of oxygen but cause significant decrements in blood pressure and elevations in PVR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 33 publications
0
26
0
Order By: Relevance
“…[16][17][18] We previously showed that slow and controlled IV infusions of lipid oxygen microbubbles (LOMs) are effective at alleviating hypoxemia. [19] Moreover, during rapid injections,L OMs increased the risk of acute pulmonary vascular obstruction because of 1) the prolonged persistence of LOMs in the blood ( Figure S7), [20] and 2) the formation of lipid aggregates as aresult of lipid shedding from the LOM shells. [19] Moreover, during rapid injections,L OMs increased the risk of acute pulmonary vascular obstruction because of 1) the prolonged persistence of LOMs in the blood ( Figure S7), [20] and 2) the formation of lipid aggregates as aresult of lipid shedding from the LOM shells.…”
Section: Microbubbles (Mbs) Play Increasingly Important Roles Inmentioning
confidence: 99%
See 1 more Smart Citation
“…[16][17][18] We previously showed that slow and controlled IV infusions of lipid oxygen microbubbles (LOMs) are effective at alleviating hypoxemia. [19] Moreover, during rapid injections,L OMs increased the risk of acute pulmonary vascular obstruction because of 1) the prolonged persistence of LOMs in the blood ( Figure S7), [20] and 2) the formation of lipid aggregates as aresult of lipid shedding from the LOM shells. [19] Moreover, during rapid injections,L OMs increased the risk of acute pulmonary vascular obstruction because of 1) the prolonged persistence of LOMs in the blood ( Figure S7), [20] and 2) the formation of lipid aggregates as aresult of lipid shedding from the LOM shells.…”
Section: Microbubbles (Mbs) Play Increasingly Important Roles Inmentioning
confidence: 99%
“…[4] However, LOMs lack sufficient stability for storage as ad rug, and are impractical for clinical use. [19] Thus,the ideal MB-based IVO 2 gas carrier should possess high storage stability,b ut be quickly cleared from the bloodstream, so that as ufficient volume of oxygen can be delivered without causing pulmonary vascular obstruction ( Figure 2A). [19] Thus,the ideal MB-based IVO 2 gas carrier should possess high storage stability,b ut be quickly cleared from the bloodstream, so that as ufficient volume of oxygen can be delivered without causing pulmonary vascular obstruction ( Figure 2A).…”
Section: Microbubbles (Mbs) Play Increasingly Important Roles Inmentioning
confidence: 99%
“…Firstly, as mentioned earlier, lipid based MBs have limited shell‐life stability. Long‐term storage of LOMs led to increased size and formation of solid lipid debris, which in turn, led to a loss in injectable gas fraction and increased the risk of pulmonary obstruction and cardiac arrest . Additionally, because lipid monolayers are brittle, LOMs are prone to rupture, resulting in free gas release, when subjected to standard injection pressures exerted during rapid i.v.…”
Section: Lipid‐based Microbubblesmentioning
confidence: 99%
“…For instance, the i.v. infusion of LOMs requires careful titration of the delivered gas fraction to avoid depletion of the local oxygen sink conditions within the vasculature; failure to do so results in prolonged microbubble persistence leading to pulmonary emboli and increased incidences of cardiac arrest (Figure D) Our laboratory has also shown that i.v. delivery of LOMs in a swine model of CA causes in vivo formation of lethal large gas emboli .…”
Section: Lipid‐based Microbubblesmentioning
confidence: 99%
See 1 more Smart Citation